Alguns apontamentos sobre a inclusão de estudante com autismo em escola de ensino regular de Rondonópolis - Lopes, Naiara de Oliveira Basílio (2020)
Including a student with autism in the regular school network, this is a very current problem and has brought with it many challenges and struggles for its effectiveness. The main objective of this study is to analyze the inclusion modality offered to the Rondonópolis municipal school. For this purpose, a bibliographic search was initially used, I do not intend to seek references on autism, as well as on situations of inclusion and segregation that the student with autism suffers at school. In addition, observations were made in classrooms (regular and resource) and interviews with three teachers, two from the regular classroom and one from the resource classroom, as a pedagogical coordinator of a school in the city of Rondonópolis, MT, to understand how the student with autism it is taken care of in the institution in question, both in the resource room and in the regular classroom. The main results show that, although the school has a room with vast and diversified pedagogical resources, it still restores some pre-lit schools, mainly for teacher training. It was also found that despite the teachers receiving continued training, there is no comprehensive training on the inclusion of a student with autism, or that hinders this action, mainly not because it comes from a regular classroom, going as or advocating the Law No. 13,146 / 2015 - Brazilian Law for the Inclusion of People with Disabilities and also the National Policy on Special Education in the Perspective of Inclusive Education (2008). In addition, there are some suggestions to contribute not to the debate on the inclusion of students with autism but not regular students. A survey also showed, through the debate and the contribution of teachers and coordinator, the need for greater investment in quality public policies that have an approach focused on the inclusion of students with autism, as it provides greater support to the faculty . I also declare through the teachers' faculty that I present through actions and documentation from the school community that I can include the permanence of students with autism spectrum in a regular classroom, provided to the person or sent to receive a quality badge that will serve to that is included in society in general.